Factors Influencing Lecturer Creativity While Using Social Media - Burkšaitienė, Nijolė; Šliogerienė, Jolita; Valūnaitė - Oleškevičienė, Giedrė (Pedagogika, 2017)
The article examines lecturer creativity in the context of social media use in the process of teaching and learning. Social media have been recently extensively used in educational settings, including higher education, and are becoming an integral part of the process of teaching and learning. Learning supported by the use of modern technologies has made creativity and its expression particularly important. The concept of creativity is multifaceted and still under development. Applying social media in the process of teaching and learning, mastering social media and using them for teaching, lecturers get involved in the continuous process, the success of which is determined by creative personal characteristics and the creativity-supportive environment. Lecturer creativity determined by the intertwined factors of the environment and personal characteristics stands out as the impetus of social media use in the process of teaching and learning. The present qualitative phenomenological research focuses on the factors influencing lecturer creativity while using social media in the process of teaching and learning at the university. The study of the phenomenon is based on lecturers’ “lived” experience while using social media in this process. Two major categories related to the factors affecting lecturer creativity were established, including external factors that promote lecturer creativity and internal factors that predetermine successful use of social media by lecturers in the process of teaching and learning.